Muscle in Variable Gravity: “I Do Not Know Where I Am, But I Know What to Do” - Monti, Elena; Waldvogel, Janice; Ritzmann, Ramona; Freyler, Kathrin; Albracht, Kirsten; Helm, Michael; De Cesare, Niccolò; Pavan, Piero; Reggiani, Carlo; Gollhofer, Albert; Narici, Marco Vincenzo (Frontiers in Physiology, 2021)
Purpose: Fascicle and sarcomere lengths are important predictors of muscle mechanical performance. However, their regulation during stretch-shortening cycle (SSC) activities in usual and challenging conditions is poorly understood. In this study, we aimed to investigate muscle fascicle and sarcomere behavior during drop-jumps (a common SSC activity) in conditions of variable gravity. Methods: Fifteen volunteers performed repeated drop-jumps in 1g, hypo-gravity (0 to 1g), and hyper-gravity (1 to 2g) during a parabolic flight. Gastrocnemius medialis (GM) electromyographic activity and fascicle length (Lf) were measured at drop-off, ground contact (GC), minimum ankle joint angle (MAJ) and push-off. GM sarcomere number was estimated by dividing Lf, measured by ultrasound at rest, by published data on GM sarcomere length, measured in-vivo at the same joint angle. Changes in sarcomere length were estimated by dividing GM Lf in each jump phase by sarcomere number calculated individually. The sarcomere force-generating capacity in each jump phase was estimated from the sarcomere length-tension relationship previously reported in the literature. Results: The results showed that, regardless of the gravity level, GM sarcomeres operated in the ascending portion of their length-tension relationship in all the jump phases. Interestingly, although in hypo-gravity and hyper-gravity during the braking phase (GC-MAJ) GM fascicles and sarcomeres experienced a stretch (as opposed to the quasi-isometric behavior in 1g), at MAJ they reached similar lengths as in 1g, allowing sarcomeres to develop about the 70% of their maximum force. Conclusion: The observed fascicle behavior during drop-jumping seems useful for anchoring the tendon, enabling storage of elastic energy and its release in the subsequent push-off phase for effectively re-bouncing in all gravity levels, suggesting that an innate neuromuscular wisdom enables to perform SSC movements also in challenging conditions.